2010
DOI: 10.1007/s10554-010-9745-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of three-dimensional rotational venography in evaluation of the left iliac vein in patients with chronic lower limb edema

Abstract: The aim of this study was to assess the role of three-dimensional rotational venography (3D RV) supplementary to two-dimensional (2D) digital subtraction venography (DSV) in evaluation of the left iliac vein in patients with chronic lower limb edema. We reviewed 34 patients with chronic lower limb edema who had undergone bilateral iliac 2D DSV and 3D RV of the left common iliac vein and had surgery in our institution. The presence, anatomical location, and size of the venous narrowing were assessed. Stenosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…17 • The RCIA crosses the LCIV transversally, and in the case of compression, LCIV deformation is "very focal" 16 and oriented along its short axis. In turn, the LCIA courses juxtaposed to LCIV lateral aspect, 18 and in the case of compression, LCIV deformation is more distal, longer, eccentric, and almost parallel to the long axis of the LCIV (Fig 4, B).…”
Section: Discussionmentioning
confidence: 99%
“…17 • The RCIA crosses the LCIV transversally, and in the case of compression, LCIV deformation is "very focal" 16 and oriented along its short axis. In turn, the LCIA courses juxtaposed to LCIV lateral aspect, 18 and in the case of compression, LCIV deformation is more distal, longer, eccentric, and almost parallel to the long axis of the LCIV (Fig 4, B).…”
Section: Discussionmentioning
confidence: 99%
“…The image is being created, thanks to the fact that the lamp in the X-ray generator revolves around the patient, during the phlebography. This visualization is peculiarly helpful in case of compression from the outside and in case of bending of the stent [5].…”
Section: Intraoperative Examinationmentioning
confidence: 99%
“…They reported a 100 % occlusion rate and that no complications or device failures were seen during follow-up. Finally, Hsieh et al [8] described the role of three-dimensional rotational venography supplementary to two-dimensional (2D) digital subtraction venography (DSV) in the evaluation of the left iliac vein in patients with chronic lower limb edema in a group of 34 patients. They concluded that in patients with negative 2D images, additional 3D RV leads to higher diagnostic sensitivity, thereby providing a powerful tool for planning surgery and endovascular treatment.…”
Section: X-ray Angiographymentioning
confidence: 99%